#### Answer

(a) 5
(b) -5

#### Work Step by Step

We are given:
$f(x)=2x-3$ and $g(x)=4-x^2$
We evaluate:
(a) $f(g(0))=f(4-0^{2})=f(4)=2(4)-3=5$
(b) $g(f(0))=g(2*0-3)=g(-3)=4-(-3)^{2}=4-9=-5$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(a) 5
(b) -5

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.